Hetero-deformation induced (HDI) stress measurement from the plastic dissipation in the hysteresis loops - Ran Chen; Guisen Liu; Peidong Wu; Yumeng Zhang; Xiaodong Wang; Yao Shen (Materials Research Letters)
Hetero-deformation induced (HDI) stress is crucial for the strengthening of heterostructured materials (HSMs), making its quantification essential for understanding the heterogeneous deformation mechanisms. We propose a novel method for measuring HDI stress based on plastic dissipation in hysteresis loops, offering superior accuracy and stability over previous methods, as demonstrated in studies on lamellar materials through experiments and FEM simulations. This approach advances a more objective, microstructure-based understanding of HDI stress in HSMs.